The Effect of Integrated Care After Discharge From Hospitals on Outcomes Among Korean Older Adults - Jae Woo Choi; Ae Jung Yoo (International Journal of Health Policy and Management, 2024)
Background  The Korean government implemented a pilot project for integrated care of older adults in June 2019. The pilot project of integrated care provided housekeeping support, nutrition support, movement assistance, home repair, consultations and education for healthy lifestyle, and some home-based primary care (HBPC) to older patients discharged from hospitals. This study investigated the outcomes of this project among older adults who participated in it after discharge from the hospital. Methods  This study combined the data from the pilot project survey with that from the National Health Insurance Service (NHIS). The participants comprised 1895 older adults who participated in the pilot project between August 1, 2019 and April 30, 2022. For comparison, 7145 older adults who lived in regions where no pilot project were selected as the matched group using propensity score matching (PSM). The length of home stay, total expenses of national health insurance (NHI) and long-term care insurance (LTCI), emergency visits, and hospital readmission for the same disease were measured, till July 31, 2022. Statistical analysis was performed through difference-in-differences (DID) analysis using a generalized estimating equation and the Cox proportional hazards model. Results  The results indicated an increase of 35.2 days (95% CI: 30.7, 39.8) in length of home stay over an average observation period of 550.5 days and a reduction of US$ 6960 (95% CI: -7,924, -5,996) in total expenses for participants compared to the controls. The odds ratio of emergency visits of the pilot project participants was 0.56 (95% CI 0.48, 0.65) compared with the controls. The hazard ratio (HR) for hospital readmission for the same disease after hospital discharge was 3.53 (95% CI: 2.98, 4.19) times higher in project participants than that in the controls. Conclusion  The pilot project for integrated care has resulted in an increased length of home stay and hospital readmission and reduced total expenses and emergency visits among older patients discharged from hospitals. The integrated care after discharge from hospitals can help older adults to continue living in the place where they lived, and improved collaboration between clinics and hospitals is required to prevent readmissions.